2022
DOI: 10.23939/jtbp2022.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Constructive Efficiency of Steel Combined Trusses

Abstract: In this article, the rational constructive form of the combined steel truss with a span of 30 meters is received, with 59% fewer elements than the typical. Calculated regulation methods are offered stress-deformation state (SDS) combined steel trusses, which make it possible to increase their efficiency. Methods of estimated SDS regulation in combined steel trusses are given: change in the stiffness of the rodsand the creation of eccentricities in the nodes connecting the lattice to the upper belt and supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In previous studies (Sydorak et al, 2022;Hohol et al, 2022), a rational structural form of a combined steel truss was found according to the following parameters: geometric (frame outline); physical (material distribution between truss elements), which will serve as our standard. For a truss with a span of 30 meters, a construction height of 2 meters was adopted, which meets the requirements of the DSTU B B.2.6-74:2008.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies (Sydorak et al, 2022;Hohol et al, 2022), a rational structural form of a combined steel truss was found according to the following parameters: geometric (frame outline); physical (material distribution between truss elements), which will serve as our standard. For a truss with a span of 30 meters, a construction height of 2 meters was adopted, which meets the requirements of the DSTU B B.2.6-74:2008.…”
Section: Methodsmentioning
confidence: 99%